Relationship Between Organizational Culture and Work Satisfaction With Commitment to Organization - Herman . (UNIVERSITAS PAKUAN, 2018)
The purpose of this study is to determine the existence of a relationship between organizational culture and job satisfaction with the commitment to the organization (Studies On Employees Tous Les Jours Bakery).Population in this research is total employee of Tous Les Jours Bakery counted 364 people, while that will be used as sample of research is 200 employee of Kitchen Staff . Based on Slovin formula 133 people are taken as samples. The research instrument is questionnaire. The obtained data is then processed by using correlation analysis techniques with the assistance of SPSS (Statistical Package for Social Science) software. The results showed that: First, the organizational culture on organizational commitment has a significant relationship and has a contribution of 11.3%. Second, job satisfaction and commitment to the organization has a very significant relationship and has a contribution of 21.7%. Eventually, both organizational culture and job satisfaction simultaneusly have a very significant relationship and have contributed 25.7%, the remaining 74.3% is determined by other unexamined variables